Impacto de las plataformas digitales en la conducta de los jóvenes de la ciudad de Santo Domingo del sector Santa Martha, en la post pandemia - Zambrano Molina, Katherine Estefanía (2021)
In this research project we will learn about topics that are very common and frequent which our young people in the SANTA MARTHA sector are living or going through due to the covid-19 pandemic, many teaching and entertainment methods were used to be able to have our young people with a calm demeanor. During all this time that we spent in restriction without being able to follow our day to day normally, for many people, digital platforms were the most used methods to be able to educate and entertain them. which also obtain information on what happens around our sector and country. It should be noted that this issue is of utmost importance because we realize what happens every day, many of us are witnesses of what went through during the post-pandemic, many young people were marked by loss of family members and these digital platforms were the best outlet to be able to have them educated and entertained at the same time.